Experimental study of the flexural strength of masonry brick walls strengthened with thermal insulation - Furtado, André (2023)
The article presents the results of a testing campaign that was carried out to validate the effect of ETICS and seismic plus energy retrofitting techniques on the flexural strength of full-scale masonry brick walls. The study highlights the importance of retrofitting techniques that can improve the energy efficiency and seismic safety of existing buildings, a growing global concern. Based on this motivation, a testing campaign was carried out to validate the effect of ETICS and seismic plus energy retrofitting to improve the flexural strength of full-scale masonry brick walls. For this, nine full-scale specimens were built where three were built without retrofitting, three with ETICS and the remaining three retrofitted with a combined retrofitting technique. Each test involved applying OOP quasi-static uniform load simultaneously at the top and bottom of each wall to reach the collapse. Also, the accuracy of prediction models for non-retrofitted and retrofitted walls will be assessed. The results indicate that retrofitting techniques can significantly improve the flexural strength of masonry brick walls, with combined retrofitting techniques showing promising results for seismic strengthening. The strength and deformation capacity improved high than 200%.